'Losing My Raise': minimum wage increases, status loss and job satisfaction among low-wage employees. (27th February 2019) - Storer, Adam; Reich, Adam
Abstract: Policymakers concerned with economic inequality regularly advocate for laws to increase the minimum wage. The impact of such laws on low-wage employment levels has been studied extensively within the field of labor economics. Yet, the vast majority of this literature has failed to explore how changes in the minimum wage impact the actual experience of low-wage work. We first discuss qualitative evidence that Walmart, the largest low-wage employer in the country, adjusts to minimum wage increases by compressing wages at the lower end of its wage distribution. We then make use of an innovative source of data to explore quantitatively the impact of such compression on workers' experiences of their jobs at Walmart. Using a difference-in-difference approach, we find that a higher minimum wage raises job satisfaction for workers who have worked at the company for under a year, but decreases job satisfaction for longer-term and marginally higher status employees.